2019
DOI: 10.3390/cells8030280
|View full text |Cite
|
Sign up to set email alerts
|

2,4 Dinitrophenol as Medicine

Abstract: In the sanctity of pure drug discovery, objective reasoning can become clouded when pursuing ideas that appear unorthodox, but are spot on physiologically. To put this into historical perspective, it was an unorthodox idea in the 1950’s to suggest that warfarin, a rat poison, could be repositioned into a breakthrough drug in humans to protect against strokes as a blood thinner. Yet it was approved in 1954 as Coumadin® and has been prescribed to billions of patients as a standard of care. Similarly, no one can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 194 publications
2
55
0
3
Order By: Relevance
“…Despite its success in reducing body weight (up to 3 lbs per week) in high doses, DNP caused substantial side effects, including rashes, cataracts, and even death due to hyperthermia (160). Nevertheless, DNP was used as an off-label weight-loss medication in the 1930s (160) and has the distinction of being one of the first drugs banned by the FDA (161). Besides direct uncoupling of oxidative phosphorylation, DNP increases intracellular cAMP, likely through the activation of adenylyl cyclase and/or inhibition of phosphodiesterase activity (160).…”
Section: Jbc Reviews: Therapeutic Regulation Of Thermogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its success in reducing body weight (up to 3 lbs per week) in high doses, DNP caused substantial side effects, including rashes, cataracts, and even death due to hyperthermia (160). Nevertheless, DNP was used as an off-label weight-loss medication in the 1930s (160) and has the distinction of being one of the first drugs banned by the FDA (161). Besides direct uncoupling of oxidative phosphorylation, DNP increases intracellular cAMP, likely through the activation of adenylyl cyclase and/or inhibition of phosphodiesterase activity (160).…”
Section: Jbc Reviews: Therapeutic Regulation Of Thermogenesismentioning
confidence: 99%
“…Nevertheless, DNP was used as an off-label weight-loss medication in the 1930s (160) and has the distinction of being one of the first drugs banned by the FDA (161). Besides direct uncoupling of oxidative phosphorylation, DNP increases intracellular cAMP, likely through the activation of adenylyl cyclase and/or inhibition of phosphodiesterase activity (160). Elevated cAMP could then activate PKA and then downstream lipolysis and thermogenesis.…”
Section: Jbc Reviews: Therapeutic Regulation Of Thermogenesismentioning
confidence: 99%
“…The main arguments in favor of Mitchell's chemiosmotic theory were based on the ability of uncouplers to cause the collapse of the membrane potential by carrying protons across membranes. At present, there is a revival of interest in uncouplers because of the growing evidence of their broad-spectrum therapeutic efficacy [1][2][3][4][5][6][7][8][9], including antibacterial potency [10][11][12][13][14][15][16][17][18][19], which was actually found very early [20]. To this end, a series of esters of fluorescein were obtained and studied at our laboratory, manifesting themselves as rather effective mitochondrial uncouplers [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Consequently, HDT drug candidates targeting the functions of macrophage, especially those involved in effective control of intracellular Mtb growth such as ROS production and autophagy, have showed promising effect against both drug-sensitive and drug-resistance Mtb infection. [9][10][11] Autophagy is critical for effective control of intracellular pathogens and mainly regulated by mTOR pathway, 12 and perturbations in the autophagy network have previously been associated with Mtb virulence 13 Accordingly, several molecules that with potential to enhance autophagy has been proposed as HDT candidate against TB. 4 , 11 The kinase PKC β lying downstream of BTK signaling has been reported as an essential regulator of AKT/mTOR signaling, 14 previous report has shown that inhibition of BTK by ibrutinib, which has been approved as firstline drug to treat chronic lymphocytic leukemia (CLL), significantly enhanced autophagy in cancer cell line glioblastoma through suppression of Akt/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%